2015
DOI: 10.1186/s12884-015-0695-9
|View full text |Cite
|
Sign up to set email alerts
|

Losing women along the path to safe motherhood: why is there such a gap between women’s use of antenatal care and skilled birth attendance? A mixed methods study in northern Uganda

Abstract: BackgroundThousands of women and newborns still die preventable deaths from pregnancy and childbirth-related complications in poor settings. Delivery with a skilled birth attendant is a vital intervention for saving lives. Yet many women, particularly where maternal mortality ratios are highest, do not have a skilled birth attendant at delivery. In Uganda, only 58 % of women deliver in a health facility, despite approximately 95 % of women attending antenatal care (ANC).This study aimed to (1) identify key fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
124
3
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(144 citation statements)
references
References 41 publications
14
124
3
3
Order By: Relevance
“…Women not receiving ANC might be unaware of their risk; advice given during ANC to deliver in a health facility has been shown to predict use of skilled facility delivery care [54,55] and ANC was strongly associated with facility delivery in this study, except in Uganda. The large majority of women (96-99%) attended at least one antenatal appointment; however, from the DHS reports for these countries, we know only around half of women attended the recommended four visits [56][57][58][59].…”
Section: Discussionmentioning
confidence: 60%
“…Women not receiving ANC might be unaware of their risk; advice given during ANC to deliver in a health facility has been shown to predict use of skilled facility delivery care [54,55] and ANC was strongly associated with facility delivery in this study, except in Uganda. The large majority of women (96-99%) attended at least one antenatal appointment; however, from the DHS reports for these countries, we know only around half of women attended the recommended four visits [56][57][58][59].…”
Section: Discussionmentioning
confidence: 60%
“…Generally, women expect to receive care promptly on reaching a health facility; therefore, long waiting times present a significant challenge to accessing health facility-based services [22, 29, 31, 53, 82, 87, 97, 107, 115, 123, 154, 155]. A shortage or absence of drugs and other essential supplies in health facilities were reported in other studies [31, 48, 56, 67, 76, 111, 115, 150, 155, 157, 163, 165168], and poor referral practices/systems [104, 105, 159, 165] such as referred clients being transported unaccompanied by healthcare staff [89], lack of feedback mechanisms on referred patients [152], and late or no referral [29] hinder efficient patient care and may result in adverse outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…However, a study using mixed method design in north Uganda showed that poor quality of care constituted a key barrier to health facility delivery. A number of respondents described their fear or past experience of being hurt, shamed, humiliated, or treated negligently at the hands of health workers (Anastasi et al, 2015). Moreover, utilization of private health services is seen as an index of wealth and status (Kesterton et al, 2010).…”
Section: Discussionmentioning
confidence: 99%